2016
DOI: 10.1093/infdis/jiw623
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Pathway Activation in Human African Trypanosomiasis

Abstract: Background.The kynurenine pathway of tryptophan oxidation is associated with central nervous system (CNS) inflammatory pathways. Inhibition of this pathway ameliorates CNS inflammation in rodent models of the late (meningoencephalitic) stage of human African trypanosomiasis (HAT). In this study, we evaluate whether the kynurenine pathway is activated in clinical HAT and associated with CNS inflammatory responses.Methods.We measured cerebrospinal fluid (CSF) tryptophan and kynurenine metabolite concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The lack of clear discrimination of disease stage by CSF metabolites is consistent with our recent observations of kynurenine pathway activation in the CNS [ 30 ] and with a recent untargeted liquid chromatography mass spectrometry study of CSF from patients infected with T. b. gambiense , where metabolic signatures were only discriminatory between early and an advanced late stage of disease defined by CSF white blood cell concentrations of >20 cells/µL [ 12 ]. Thus, metabolic alterations and neuroinflammatory activation appear to be predictive of neurological sequelae in HAT but not of diagnostic stage.…”
Section: Discussionsupporting
confidence: 88%
“…The lack of clear discrimination of disease stage by CSF metabolites is consistent with our recent observations of kynurenine pathway activation in the CNS [ 30 ] and with a recent untargeted liquid chromatography mass spectrometry study of CSF from patients infected with T. b. gambiense , where metabolic signatures were only discriminatory between early and an advanced late stage of disease defined by CSF white blood cell concentrations of >20 cells/µL [ 12 ]. Thus, metabolic alterations and neuroinflammatory activation appear to be predictive of neurological sequelae in HAT but not of diagnostic stage.…”
Section: Discussionsupporting
confidence: 88%
“…Briefly, oxidation of L-tryptophan to kynurenine is catalyzed by the indoleamine 2,3-dioxygenase (IDO), while the non-enzymatic cyclization of kynurenine forms the quinolinate, which in turn can be converted to niacin. On the other hand, L-tryptophan can be transformed to form serotonin (neurotransmitter), which can be metabolized further to produce melatonin (neuro-hormone) [12]. Investigations have revealed that oxidative stress resulting from ROS production can affect the immune activity and neurotransmitter levels by influencing neurotransmitter synthesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…54 Activation of this pathway has been found through liquid chromatography-mass spectrometry analysis of CSF samples from patients with both early and late-stage HAT. 53 In these patients, significant increases in kynurenine levels, accompanied by decreased tryptophan concentrations, were observed in infected individuals compared to uninfected controls. 53 An association was also found between tryptophan catabolism and increased CSF IL-6 concentrations, providing further evidence to support a role for this pathway in the neuropathogenesis of HAT.…”
Section: Neuropathogenesismentioning
confidence: 83%
“…53 In these patients, significant increases in kynurenine levels, accompanied by decreased tryptophan concentrations, were observed in infected individuals compared to uninfected controls. 53 An association was also found between tryptophan catabolism and increased CSF IL-6 concentrations, providing further evidence to support a role for this pathway in the neuropathogenesis of HAT. Changes in the concentration of kynurenine pathway metabolites in the CSF were also identified in a metabolomics study, designed to detect potential biomarkers for late-stage HAT, although these changes were small.…”
Section: Neuropathogenesismentioning
confidence: 83%
See 1 more Smart Citation